2013
DOI: 10.1016/j.pain.2013.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for working memory deficits in chronic pain: A systematic review and meta-analysis

Abstract: People with chronic pain commonly report impaired cognitive function. However, to date, there has been no systematic evaluation of the body of literature concerning cognitive impairment and pain. Nor have modern meta-analytical methods been used to verify and clarify the extent to which cognition may be impaired. The objective of this study was to systematically evaluate and critically appraise the literature concerning working memory function in people with chronic pain. The study was conducted along Cochrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
199
1
8

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(228 citation statements)
references
References 63 publications
20
199
1
8
Order By: Relevance
“…Reports about working memory functions are common across a wide variety of chronic pain states and, as reviewed by Berryman et al, moderate impairment in working memory can be consistently observed across studies and paradigms (35). Consistent with previous studies showing a slowdown in the response processing of FM patients (36), our patients were slower in selecting whether the target was similar to or different than a previous stimulus.…”
Section: Discussionsupporting
confidence: 89%
“…Reports about working memory functions are common across a wide variety of chronic pain states and, as reviewed by Berryman et al, moderate impairment in working memory can be consistently observed across studies and paradigms (35). Consistent with previous studies showing a slowdown in the response processing of FM patients (36), our patients were slower in selecting whether the target was similar to or different than a previous stimulus.…”
Section: Discussionsupporting
confidence: 89%
“…Some previous studies, have associated psychological aspects to problems in cognitive areas 14 and others results have indicated that, independently of depressive symptoms, basic neurocognitive functions are impaired in patients with severe chronic pain 15 . Therefore, the main objective of the present study was to describe and analyze the cognitive evaluation of patients with chronic pain compared to control subjects with no pain.…”
mentioning
confidence: 98%
“…Pain is a hardwired signal of bodily harm, and is designed to capture attention, and to interrupt ongoing activities (Eccleston & Crombez, 1999;Gatzounis, Schrooten, Crombez, & Vlaeyen, 2014. There is a wealth of experimental studies that demonstrate this automatic function of pain (Moore, Keogh, & Eccleston, 2012) (Berryman et al, 2013). In an example of the primary task paradigm, participants perform as quickly as possible an auditory discrimination task in the presence or absence of painful stimuli (Crombez, Eccleston, Baeyens, & Eelen, 1996.…”
Section: The Interruptive Function Of Painmentioning
confidence: 99%